Antagonistic effects of selenium on lead-induced autophagy by influencing mitochondrial dynamics in the spleen of chickens - Han, Yujing; Li, Chunqiu; Su, Mingjun; Wang, Zhihui; Jiang, Ning; Sun, Dongbo (Oncotarget, 2017)
Lead (Pb) may damage the immune function in human and animal. Selenium (Se) has antagonistic effects on Pb. In our study, brown layer chickens were randomly allocated to control group, Se group (1 mg/kg Se), Se+Pb group (1 mg/kg Se and 350 mg/kg Pb), and Pb group (350 mg/kg Pb). The chickens were sacrificed on the 90th day; spleen tissues were subjected to observation of ultrastructure and detection of spleen-related indexes. The results revealed that in the Pb group, expression levels of the cytokines IL-1 and TNF-α significantly increased, and expression levels of IL-2 and INF-γ significantly decreased; activities of antioxidant enzyme GPX, SOD and CAT significantly decreased, and expression level of malondialdehyde (MDA) significantly increased; expression levels of mitochondrial fission-related genes (Mff and Drp1) significantly increased, and expression levels of mitochondrial fusion-related genes (Opa1, Mfn1 and Mfn2) significantly decreased; expression of autophagy-related genes (Beclin 1, Dynein, Atg 5, LC3-I and LC-II) was upregulated, while expression of mammalian target of rapamycin (mTOR) was downregulated. The results of transmission electron microscopy indicated that Pb induced mitochondrial fragmentation, and triggered autophagy in the spleen of chickens. The Se and Pb co-treatment remarkably alleviated these injuries induced by Pb in the spleen of chickens. In conclusion, Pb can induce the oxidative stress to influence the mitochondrial dynamics balance and lead to autophagy, which triggers the immune dysfunction in the spleen of chickens; the Se exhibits the antagonistic effects on lead-induced autophagy by influencing mitochondrial dynamics in the spleen of chickens.